Large effects of brief meditation intervention on EEG spectra in meditation novices. (December 2020) - Stapleton, P.; Dispenza, J.; McGill, S.; Sabot, D.; Peach, M.; Raynor, D.
Highlights: Novice meditators achieved large varying effects on EEG outcomes across all power bands. Transition into coherent theta brain wave patterns were up to ten standard deviations outside the normal range. The speed of change from pre-meditation to post-meditation states of the EEG co-spectra was significant in novices. Clinical examination of meditation recommended as an intervention for stress in novice meditators. Abstract: This study investigated the impact of a brief meditation workshop on a sample of 223 novice meditators. Participants attended a three-day workshop comprising daily guided seated meditation sessions using music without vocals that focused on various emotional states and intentions (open focus). Based on the theory of integrative consciousness, it was hypothesized that altered states of consciousness would be experienced by participants during the meditation intervention as assessed using electroencephalogram (EEG). Brainwave power bands patterns were measured throughout the meditation training workshop, producing a total of 5616 EEG scans. Changes in conscious states were analysed using pre-meditation and post-meditation session measures of delta through to gamma oscillations. Results suggested the meditation intervention had large varying effects on EEG spectra (up to 50 % increase and 24 % decrease), and the speed of change from pre-meditation to post-meditation state of the EEG co-spectra was significant (with 0.76 probability of entering end-meditation state within the first minute). There was a main 5 % decrease in delta power (95 % HDI = [−0.07, −0.03]); a global increase in theta power of 29 % (95 % HDI = [0.27, 0.33]); a global increase of 16 % (95 % HDI = [0.13, 0.19]) in alpha power; a main effect of condition, with global beta power increasing by 17 % (95 % HDI = [0.15, 0.19]); and an 11 % increase (95 % HDI = [0.08, 0.14]) in gamma power from pre-meditation to end-meditation. Findings provided preliminary support for brief meditation in altering states of consciousness in novice meditators. Future clinical examination of meditation was recommended as an intervention for mental health conditions particularly associated with hippocampal impairments.